1980
DOI: 10.1152/ajpheart.1980.238.4.h423
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hemodynamic responses to occlusion of the descending thoracic aorta

Abstract: To examine left ventricular responses to aortic occlusion, changes in end-diastolic volume (EDV) and end-systolic volume (ESV) were estimated by ultrasonic recordings of myocardial distances in atropinized open-chest dogs. During aortic occlusion EDV and ESV increased equally, systolic left ventricular pressure (LVP) rose by 86 +/- 8 mmHg, and blood flow more than doubled in the superior vena cava and fell by 90% in the inferior vena cava. During combined occlusion of aorta and inferior vena cava, systolic LVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0
3

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 0 publications
3
40
0
3
Order By: Relevance
“…There were no changes in any of the venous circulation parameters including resistance to venous return. Our data are consistent with the classical studies of Herndon and Sagawa (1) and Stokland et al (19,20). These investigators showed that cardiac output was independent ofafterload up to a mean aortic pressure of 180 mmHg (1).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There were no changes in any of the venous circulation parameters including resistance to venous return. Our data are consistent with the classical studies of Herndon and Sagawa (1) and Stokland et al (19,20). These investigators showed that cardiac output was independent ofafterload up to a mean aortic pressure of 180 mmHg (1).…”
Section: Discussionsupporting
confidence: 93%
“…These investigators showed that cardiac output was independent ofafterload up to a mean aortic pressure of 180 mmHg (1). As afterload increases there is a redistribution of cardiac output and left ventricular filling is maintained (19). Left (22).…”
Section: Discussionmentioning
confidence: 99%
“…11 Intra-aortic balloon counterpulsation has been demonstrated to improve cerebral blood flow in both animals 12 and humans, 13 but the complex algorithms required to achieve increases in cerebral blood flow have limited clinical adoption in patients with acute stroke. Complete aortic occlusion of either the descending thoracic aorta or the abdominal aorta above the renal arteries results in a prompt increase in blood volume above the occlusion 14,15 and has been shown to specifically increase cerebral blood volume. 14 Interestingly, the increase in blood flow persisted when the balloons were withdrawn.…”
mentioning
confidence: 99%
“…Data from animal models and from human research demonstrate that aortic occlusion, which is commonly performed by crossclamping the descending aorta for vascular control during aortic surgery, results in net flow diversion to the cerebral from the lower-extremity circulatory beds, thereby increasing cerebral blood flow. [707][708][709][710][711][712][713][714][715] This evidence generated the development of a catheter-based device with 2 balloons near its distal tip placed in the infrarenal and suprarenal positions in the descending aorta (NeuroFlo device; CoAxia, Maple Grove, MN). After insertion via the femoral artery, the balloons are inflated sequentially up to ≈70% of the diameter of the aortic lumen over a period of 45 minutes to an hour, followed by removal.…”
Section: Mechanical Flow Augmentationmentioning
confidence: 99%